Can local institutions reduce poverty? : rural decentralization in Burkina Faso - Donnelly-Roark, Paula, 1941- 1941- (Policy research working paper, 2001)
Can local institutions take a lead role in reducing poverty? In the past the answer would have been an emphatic no. Local institutions have traditionally been a blind spot for national government and international development agencies. But high-performing local institutions in Burkina Faso have reduced poverty and inequality. Can this model of rural decentralization spark a reinvention of development models across Africa, using indigenous development institutions to reduce poverty and promote equitable growth?